Microtox 생물검정법을 이용한 하수오니 처리 토양의 독성평가 - 박상준; 김승기; 남재작 (한국환경분석학회, 2006)
The toxicity of soils treated with sewage sludge was evaluated using Microtox instrumental analysis. In soils treated with highly polluted sewage sludge from industrial zone, the bioassay revealed a high potential toxicity in proportion to the amount of sewage sludge. In soils treated with highly polluted sewage sludge from municipal zone contained the low level of heavy metals, PAHs. The effect of Microtox concentration was well correlated with the concentration of heavy metals and PAHs on soils. This bioassay technique can be a sensitive method of soil quality evaluation and useful for discriminating the quality of soil following potential risk assessment.